2015
DOI: 10.1080/05704928.2015.1054498
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of Lanthanides Ion in High-Temperature Molten Salt

Abstract: Spectroscopic studies for lanthanide elements in molten salt media performed using absorption, fluorescence, infrared, Raman, electron spin resonance spectroscopy (EPR), and M€ ossbaur spectroscopy were reviewed in an effort to understand the effect of structural change and chemical behavior of lanthanides on the temperature increase and the matrix change. The absorption spectroscopic studies revealed electronic energy levels of the transitions with the general structural information of the lanthanide elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Hypersensitive f-f-transition 4 I 15/2 → 4 G 11/2 of erbium(III) was located at almost the same wavelength (379 nm). [23] Thus, 4f-luminescence observed under excitation at 371 nm was a result of both intramolecular transfer from phthalocyanine and in a less degree from porphyrin chromophores and direct excitation of Er(III) ion. So, this "three-component" 4f-luminescence had a value of 8450 a.u.…”
Section: Uv-vis Spectrum Of Heteroleptic Double-decker Complex [(15c5mentioning
confidence: 97%
“…Hypersensitive f-f-transition 4 I 15/2 → 4 G 11/2 of erbium(III) was located at almost the same wavelength (379 nm). [23] Thus, 4f-luminescence observed under excitation at 371 nm was a result of both intramolecular transfer from phthalocyanine and in a less degree from porphyrin chromophores and direct excitation of Er(III) ion. So, this "three-component" 4f-luminescence had a value of 8450 a.u.…”
Section: Uv-vis Spectrum Of Heteroleptic Double-decker Complex [(15c5mentioning
confidence: 97%
“…In molten chloride salts, lanthanides such as Nd, Eu, Ce, and Ho are observed to exist predominantly in their Ln­(III) oxidation state and form octahedrally coordinated LnCl 6 3– anionic complexes as measured by spectrophotometric techniques. The octahedral coordination complex has also been demonstrated in a variety of RTIL systems such as in the chloroaluminate melt and a variety of chloride-doped hydrophobic RTILs. Electrochemical investigations of lanthanides exhibiting an accessible Ln­(III/II) couple also reveal fast, reversible electron transfer characteristics through cyclic voltammetry (CV) and suggest that electron transfer is dominated by outer-sphere effects. , Further, they demonstrate that the Cl – ligand has a strong stabilizing effect on the Ln III oxidation states and is reflected as a negative shift in their reduction potentials . These influences of the salt electrolyte environment were corroborated by MacInnes et al who found that the molten salt cation polarization strength played a significant role in the stability of lanthanide chloride anionic complexes due to outer-sphere coordination effects .…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Several mechanisms for redox control have been developed 3 and molten salt samples can be retrieved from the reactors in order to provide chemical characterization with electrochemical and spectroscopic methods. [7][8][9] In situ chemical analysis can be realized through X-ray absorption spectroscopy and the determination of thermophysical properties through laser flash analysis and high-temperature calorimetry. 6 As a wide range of vapors, salt mists, pyrolysis products, and aerosols may be generated during the operation of an MSR, 8 our research has been focused on the development of methods for the generation and chemical identification of off-gassed products under simulated MSR conditions.…”
Section: Introductionmentioning
confidence: 99%